Factors influencing the help-seeking behavior in patients with mild cognitive impairment: a qualitative study - Yu-Chen Jiao; Jing Chang; Chang Liu; Shi-Yu Zhou; Yan Ji; Yao Meng (BMC, 2023)
Abstract Background The early diagnosis and intervention of mild cognitive impairment (MCI) patients is expected to delay the progression of AD. Delayed treatment will lead to MCI patients missing the best intervention expectation. At present, the medical help-seeking behavior of this group is not optimistic. This study aimed to explore influencing factors of help-seeking behavior among patients with MCI in China based on the help-seeking behavior model. Methods Twenty-two patients with MCI were recruited to participate in semi-structured interviews via purposeful sampling with a qualitative, descriptive design. Data were analyzed by qualitative content analysis. Results The study revealed the main influencing factors of help-seeking behavior among MCI patients in China included perceived disease threat, symptom attribution, disease knowledge, use of cognitive compensation strategies, sense of foreseeable burden, social support, economic condition, and accessibility of medical service. Conclusions The help-seeking behavior of patients with MCI is affected by multiple factors. There are some key factors in different stages of the help-seeking process. Healthcare providers can utilize these factors to design targeted interventions for promoting early help-seeking of patients with MCI.